Strategies and Challenges of Inclusive Education in Indonesia: Strategi dan Tantangan Pendidikan Inklusif di IndonesiaStrategi dan Tantangan Pendidikan Inklusif di Indonesia - Ananda Asti Putri; Syaid Ali Jailani (Syamilah Publishing, 2024)
This study aims to identify the main challenges in implementing inclusive education in Indonesia and offer solution strategies to overcome them. The research method used is a literature review by analyzing relevant sources such as journals, books, and other literature. The research findings identify several main challenges, including a lack of supporting facilities for the inclusive system, limited teacher competence, a curriculum that has not accommodated student diversity, negative societal stigma, inadequate school management, and a lack of collaboration among stakeholders. The recommended solution strategies include providing accessible infrastructure, increasing teacher capacity through continuous training, developing an inclusive curriculum, campaigning to raise public awareness, government support in providing resources, and cooperation and synergy among various related parties. This research concludes that optimizing the implementation of inclusive education requires strong commitment and collaboration from all stakeholders.